Answer:
i love algebra anyways
the ans is in the picture with the steps
(hope it helps can p lz have brainlist it will make my day
Step-by-step explanation:
<span>3x + 3 − x + (−7) > 6
2x - 4 > 6
2x > 10
x > 5
answer is </span><span>C. x > 5 </span>
Answer:
a = 1, b = 7
Step-by-step explanation:
Given the 2 equations
3a + 6b = 45 → (1)
2a - 2b = - 12 → (2)
Multiply (2) by 3 and add to (1) to eliminate the term in b
6a - 6b = - 36 → (3)
Add (1) and (3) term by term
(3a + 6a) + (6b - 6b) = (45 - 36)
9a = 9 ( divide both sides by 9 )
a = 1
Substitute a = 1 in either (1) or (2) and solve for b
(1) → 3 + 6b = 45 ( subtract 3 from both sides )
6b = 42 ( divide both sides by 6 )
b = 7
For example, think about 8.4 - 2.9.
You have to regroup because you can't subract 4 - 9.
4 turns into a 14 since you borrow from the left number, 8.
8 turns into a 7 after that.
Now, you have to subtract 14 - 9 and 7 - 2. You're answer is 5.5.
You can check your work by doing inverse opperations:
By adding:
5.5 + 2.9 = 8.4
Or by subracting 8.4 - 5.5 = 2.9
Hope this helped you! If you need a better explaination or another example, I will be happy to help you! :)